Cane molasses in rations of growing beef calves. The value of winter shelter for feedlot calves - Smith, E.F.; Richardson, D.; Deyoe, C.W.; Curtis, R.G.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Choice grade Hereford steer calves in this test came from near Alden, Kansas, and were assigned to treatments on a random-weight basis. All lots received the same experimental diet except 10 percent molasses was substituted for grain in the self-fed mixture for two lots. Small adjustments were made to equalize protein and energy intake between molasses and no-molasses lots. The composition of the roughage-concentrate mixture is listed in Table 52; it consisted primarily of ground rice hulls, ground sorghum grain, additives and other nutrients, including additional protein.
Keywords: Beef; Cane molasses; Protein; Shelter